New advancements in the management of Neuromyelitis Optica spectrum disease: literature review - Sudhakar, Padmaja; Abusamra, Khawla; Thandampallayam, Mangayarkarasi; Kini, Ashwini (Frontiers in Ophthalmology, 2023)
Neuromyelitis Optica spectrum disorder (NMOSD) is a relapsing autoimmune antibody-mediated disease of the brain and spinal cord where aquaporin-4 water channels (WC) are the antigenic target of the disease. The spectrum of the disease involves regions of the central nervous system (CNS) where the WC are widely expressed including spinal cord (longitudinally extensive transverse myelitis- LETM), optic nerve (optic neuritis-ON), dorsal medulla (area postrema syndrome), brainstem (acute brainstem syndromes), and thalamus/hypothalamus (acute diencephalic syndromes). Treatment of NMOSD includes acute as well as long term treatment. Acute relapses are typically treated with high dose intravenous steroids and/or plasma exchange and long-term treatment involves the use of immunosuppression/immune modulation. The year 2019 is thought to be the “year of the NMOSD” as 3 new medications became available for this devastating disease. In this review, FDA approved NMOSD medications are discussed.